Platelet-Rich Plasma (PRP) As A New Approach And Promising Therapy In Patients With Alopecia Areata - Ametati, Holy; Kadarhadi, Elva; Gunawan, Imelda; Malik, Diah Adriani; Rahayu, Muji (Medica Hospitalia : Journal of Clinical Medicine, 2023)
Background: Alopecia areata (AA) is a non-scarring, autoimmune, inflammatory condition that causes well-defined areas of hair loss on the scalp and/or body. A new biotechnology called platelet-rich plasma (PRP) was developed as a result of increased interest in tissue engineering and cell-based therapies. This therapy is defined as an autologous, non-allergic preparation of platelets in concentrated plasma. Study aimed to evaluate the effect of PRP treatment in alopecia areata. Case: This study included 3 patients complaining of multiple patchy alopecia areata. They were treated with combination of PRP therapy, topical fluocinolone acetonide 0.025% cream, minoxidil 2 and 5%, and ketoconazole 2% scalp solution. One patient was also treated with intralesional triamcinolone acetonide injections. PRP was injected intradermally every 4 weeks and final monitoring was conducted after 4-6 sessions. Evaluation and follow up results were determined using photographic monitoring as well as patient’s satisfaction. Results: Administration of autologous PRP had significance hair regrowth in all three patients in this study. PRP treatment sessions varied from 3 to 6 sessions. However, significance outcomes in these patients were established after 3 sessions of PRP treatment, while the best results were obtained after 4-6 sessions of PRP treatment. No major side effects was reported. Conclusion: PRP is effective in promoting hair growth. PRP treatment for alopecia areata is safe, easy to perform, and can achieve patient’s satisfaction, without any major adverse effects. However, further research on standardized protocol of PRP methods are needed.